Pengaruh Penerapan Formasi Tempat Duduk Tipe U Terhadap Konsentrasi Belajar Siswa Pada Mata Pelajaran Sejarah Kebudayaan Islam di MTsM Lawang Tigo Balai - Yuliandri, Resa Afri; Abdul Karim, Hamdi; Aprison, Wedra; Rahmi, Ulva (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research is motivated by the importance of student concentration when learning takes place. One factor that can influence student learning concentration is classroom management. Class management arrangements will create enthusiasm and concentration in learning, one of which is the arrangement of seating formations, including the Type U seating formation. The aim of this research is to determine the effect of implementing the U type seating formation on the learning concentration of class VIII students in SKI subjects in MTsM Lawang Tigo Balai,. This research uses a Quasi Experimental research method. The sample for this research is class VIII students at MTsM Lawang Tigo Balai with a sample size of 52 students. The research sample is class VIII 2 as an experimental class which uses a U-type seating formation and class VIII 3 as a control class which still uses a conventional (ordinary) seating formation. The data analysis technique uses the Normality Test, the Homogeneity Test and Hypothesis Testing. The research results show that the hypothesis results mean the experimental class is greater than the control class, namely 45.04 41.31 and the sig data is 0.892 0.05, which means Ho is rejected and Ha is accepted. This means there is a significant influence on implementation. U-type seating formation on student learning concentration in class VIII SKI subjects at MTsM Lawang Tigo Balai.